2020
DOI: 10.3354/meps13521
|View full text |Cite
|
Sign up to set email alerts
|

Critical threshold identified in the functional relationship between beaked whales and their prey

Abstract: Anthropogenic noise is increasingly recognized as a potentially significant stressor for marine animals. Beaked whales, deep-diving cephalopod predators, have been disproportionally present in atypical mass stranding events coincident with military sonar exercises, while frequently disturbed populations that do not strand may have reductions in fitness. We present in situ measures of prey availability, a key factor affecting fitness, for 2 distinct populations of Mesoplodon densirostris: one on a US Navy range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 56 publications
(68 reference statements)
0
29
0
Order By: Relevance
“…Here, intense surface and diffuse deep scattering layers were identified at depths of ∼120 and ∼540 m, respectively, during the daytime, becoming more intense and migrating shallower at night (Sato and Benoit-Bird, 2017). Our sampling location has been identified as a high-quality foraging habitat for odontocetes, with high density in mesopelagic scattering layers at ∼150 and ∼700-800 m (Benoit-Bird et al, 2020). Thus, the depths of both our array and the majority of our Kogia localizations (Table 1) overlap with scattering layers at this location, supporting our hypothesis that they are foraging in acoustically cluttered prey layers.…”
Section: Source Level and Biosonar Detection Rangesmentioning
confidence: 66%
“…Here, intense surface and diffuse deep scattering layers were identified at depths of ∼120 and ∼540 m, respectively, during the daytime, becoming more intense and migrating shallower at night (Sato and Benoit-Bird, 2017). Our sampling location has been identified as a high-quality foraging habitat for odontocetes, with high density in mesopelagic scattering layers at ∼150 and ∼700-800 m (Benoit-Bird et al, 2020). Thus, the depths of both our array and the majority of our Kogia localizations (Table 1) overlap with scattering layers at this location, supporting our hypothesis that they are foraging in acoustically cluttered prey layers.…”
Section: Source Level and Biosonar Detection Rangesmentioning
confidence: 66%
“…Combined data on deep-sea prey spectra available in cetacean target foraging zones also represent critical knowledge aiding in the understanding of marine top predator foraging performance and how this may change under disturbance settings. Absence of knowledge on prey communities has been identified as a limiting factor in the understanding of population-level effects of predator behavioral responses causing impeded foraging, particularly for beaked whales, which are highly sensitive to disturbance from anthropogenic noise ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Abecassis et al (2015) found that a high density of midwater micronekton was an important covariate for Blainville's beaked whale distribution off the island of Hawai'i, likely because it represents the prey for beaked whale food sources. Benoit-Bird et al (2020) found that additional oceanographic features highly correlated with beaked whale habitat were associated to deep-sea squid habitat, highlighting the importance of these focused food sources. When Suntsov and Domokos (2013) sampled micronekton and macro zooplankton on three meridional transects between 10 • N and 17 • N in the Mariana Archipelago, they found relatively low concentrations within the oligotrophic NEC suggesting the prey availability for beaked whale and Kogia spp.…”
Section: Environmental Modelingmentioning
confidence: 94%